2023
DOI: 10.3390/coatings13020362
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-Based Zinc Oxide Nanoparticles Coating Extends Storage Life and Maintains Quality Parameters of Mango Fruits “cv. Kiett”

Abstract: In this study, we describe the synthesis of zinc oxide nanoparticles (ZnO NPs) and evaluate the impact of alginate-based ZnO NPs (Alg–ZnO NPs) on microbiological activity, storage behavior, and physico-chemical properties of ‘Kiett’ mango fruit. The fruits were coated with alginate and Alg–ZnO NPs and then stored at 13 °C; uncoated mango fruits were used as controls. ZnO NPs were synthesized and characterized, confirming the formation of spherically shaped particles with sizes ranging from 12 to 15.1 nm and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Table 3 shows the Brix and TSS of coated mango fruits. The changes in TSS observed during storage may be a result of the breakdown of complex carbohydrates by hydrolytic enzymes [43]. TSS should remain consistent with the natural sugar levels, as the coatings primary function is moisture and microbial control.…”
Section: Total Soluble Solid (Tss) Ph and Titratable Aciditymentioning
confidence: 97%
See 3 more Smart Citations
“…Table 3 shows the Brix and TSS of coated mango fruits. The changes in TSS observed during storage may be a result of the breakdown of complex carbohydrates by hydrolytic enzymes [43]. TSS should remain consistent with the natural sugar levels, as the coatings primary function is moisture and microbial control.…”
Section: Total Soluble Solid (Tss) Ph and Titratable Aciditymentioning
confidence: 97%
“…The decrease in permeability of oxygen and moisture can be ascribed to the barrier qualities of the ller material [42]. Climacteric mature fruit experiences a sequence of metabolic transformations when detached from the tree, and these metabolic activities ultimately lead to a reduction in fruit weight throughout the postharvest and storage duration [43].…”
Section: Weight Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…found that apple sprayed with zinc oxide had lower pH values when compared with control samples (Rasouli and Saba 2018). Hmmam et al (2023) reported reducing trend in titratable acidity of mango fruit during storage(Hmmam et al 2023). They stated that alginate-based zinc oxide nanoparticles caused to increase in titratable acidity of coated samples in comparison to control sample.…”
mentioning
confidence: 99%